Diffractive structures for testing nano-meter technology - Blattner, Peter; Naqvi, S. S. H.; Herzig, Hans-Peter; Ehbets, Peter (My University, 1995)
We investigated two optical methods for characterizing submicron structures. Average errors of a few nanometers can be determined by the far-field diffraction metrology utilizing diffractive structures having enhanced sensitivity to fabrication errors. The scanning spot metrology is well suited for analyzing lithographic masks.